Management of pregnancy failure in cows with vaginal stimulation and hormone therapy (Bangladesh Veterinarian, 2023)
The focus of this study is to improve the pregnancy rate of cattle using different interventions with the analysis of associated risk factors. A total of 180 cows with pregnancy failure after one insemination were selected, which showed normal oestrous behaviour and vaginal mucus discharge. The animals were divided into six groups: A [control: with only Artificial Insemination (AI)]; B [penis-like device (PLD) used after AI]; C [intramuscular injection (im) of 2 ml prostaglandin-F2α at day 7 of the oestrous cycle and AI at observed oestrus], D [AI at natural oestrus followed by 2.5 ml GnRH im, repeated 4-6h after AI], group E [As group C and PLD used after AI], group F [as D and PLD used after AI]. The overall pregnancy was 55.6%. Group F had the highest pregnancy rate (70.0%). Higher pregnancy rates were in older animals of more than 4.6 years of age with parity of more than two. A significant correlation was found between age and parity; age and Artificial Insemination Technician (AIT); Body Condition Score (BCS) and breed; Reproductive Health (RH) and AIT. It is suggested that the use of hormonal treatments (with or without PLD) improved the pregnancy rate in cattle.Bangl. vet. 2022. Vol. 39, No. 1-2, 16–25